GAYA PENGASUHAN OTORITER DAN PERILAKU BULLYING DI SEKOLAH MENURUNKAN SELF-ESTEEM ANAK USIA SEKOLAH - Pratama, Andriansyah Adha; Krisnatuti, Diah; Hastuti, Dwi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2014)
This research was conducted to examine parenting style, bullying in school, and self-esteem of school-aged children; differences of these variables based on children sex; correlation among variables; and influence of family charactristics, children characteeristics, parenting style, and bullying in schools on self-esteem of schoolaged children. Particpants of this research were 100 students grade 4 and 5 of three public elementary schools; these schools were located in Ciracas Sub District, East Jakarta. Data were collected by self-report of participants. Data analysis used independent sample t-test, correlation test, and multiple regression analysis. The result showed that parenting styles had significant correlation with children sex. The boys tend to be raised with authoritarian parenting style; but the girls tend to be raised with authoritative parenting style. Based on the highest proportion, boys tend to bully others in school but girls tend to be victim of bullying. Authoritarian and victim of verbal bullying positive significantly influenced on decreasing of self-esteem. The result indicated that parents who conduct authoritarian style can cause decreasing self-esteem in school-aged children. The children who became victim of bullying in school also can decrease their self-esteem.